Knowledge Sharing, Competence, and Teamwork as Predictors of Employee Performance: Evidence From PT Pegadaian Gianyar Branch - Ni Kadek Valentina Febiyanti; Nengah Suardikha; I Gede Rihayana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
Digital transformation and increasing business competition require companies to optimize the quality of their human resources, including at PT Pegadaian Gianyar Branch. Performance data indicates fluctuations in KPIs and the consistent failure to meet micro-targets during the 2020–2024 period. This situation indicates the presence of internal barriers related to low knowledge-sharing practices, competency gaps, and ineffective teamwork. This study aims to analyze the influence of knowledge sharing, competency, and teamwork on employee performance. The study employs a quantitative approach with a population of 41 employees, all of whom were selected as the sample using a saturated sampling technique. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that all three variables—knowledge sharing, competencies, and teamwork—have a positive and significant influence on employee performance. Knowledge sharing enhances performance through clear information dissemination, sharing of experiences, and the exchange of ideas that support work effectiveness. Competence exerts the greatest influence through mastery of SOPs, technical skills, and decision-making ability. Teamwork contributes to improved performance through effective communication, task coordination, and mutual support among team members. Overall, these three variables play a crucial role in fostering optimal and sustainable employee performance at PT Pegadaian’s Gianyar Branch.